(untitled) (Tecno-Lógica, 2021)
The periodic maintenance of agricultural sprayers is essential to ensure safe spraying from an environmental point of view and technically efficient, with respect to acceptable quality limits. Aiming to optimize the use of pesticides for protecting farming, many countries worldwide have been developing projects on the inspection of agricultural sprayers. In Brazil, regardless its tradition of being an agricultural country, still now these inspections are done in a voluntary way, showing that most agricultural sprayers are not in use conditions, which can affect the technical efficiency of the operation, offer a risk of environmental contamination and, intoxication of the operator. This review aim describe the results got through projects on inspection of agricultural sprayers in different Brazilian regions. The methodology was based on the survey of data published in scientific articles and thesis. The most serious problems detected in those agricultural sprayers are mainly in terms of absence of environmental and user safety, no protection of the cardan tree, of belts and pulleys as well as leakage occurrence. Furthermore, the most common problems related to spraying activities are those of manometer precision as well as those of worn spray nozzles and spray transverse distribution wear and tear that in all justifies the obligation for technical inspection of agricultural sprayers in Brazil. Besides that, it is important to emphasize the necessity of public policies for development and approval of research centers for tests on agricultural implements.